FISH FARMING ACTIVITY IN MAYSAN GOVERNORATES - Jabir, A. A.; Youns, K.H.; AL Mossawy, M.H . (Iraqi Journal of Aquaculture, 2022)
A field survey had been done for 41 fish farms in the districts of Maysan governorate during 2008.The Results showed that the highest number of fish farms was at the centre of the city of Amarah and Alkahala(24.4%). The highest number of fish farms (16) was established during 2007.The total area of the fish farms is 1262.5donam (donam= 1/4 hectare). The largest water area was found in Almejar (853 donam= 67.5%) and the lowest area in Almaemona (13 donam= 2.44%.). The number of farms with area less than 10 donam were 26 farms (63.4%). The highest number recorded in Almaemona district (30.8%), while the farms less than 50 donam were 13 farms (31.7%). Only one farm more than 100 donam was found in the district of Almejar. The highest proportion of dyke pond farms was in the district of Almejar (16.66%). Three methods were used to fill the ponds were diesel pumps, electricity and runoff, with a proportion of 57.4%, 33.33%, 9.25% respectively. The pliers for the fingerlings were either the hatchery of Marine Sciences Centre(25%), Al Suwayrah Hatchery(51%), farmer ponds or the environment. Highest number of farmed fish was 1181100 fish of C.carpio (84.5% of the total number).